P026 Impaired cerebellum to motor cortex associative plasticity in spinocerebellar ataxia. Issue 3 (March 2017) - Lu, M.-K.; Chen, C.-M.; Duann, J.-R.; Chen, J.-C.; Tsai, C.-H.
Abstract : Introduction: The previous evidence has showed that bidirectional spike-timing dependent plasticity (STDP)-like plasticity in primary motor cortex (M1) can be mediated by associative stimulation of the cerebello-dentato-thalamo-cortical (CDTC) pathway and M1 in young healthy adults. The pattern of such plasticity has never been studied in patients with cerebellar degeneration. Objectives: To compare the corticocortical paired associative stimulation (PAS)-induced STDP-like plasticity between healthy subjects and patients with hereditary spinocerebellar ataxia (SCA). Patients & methods: Seven gene-confirmed patients with SCA (5 with type 3, 2 with type 2) and nine healthy subjects were studied. One hundred and twenty pairs of transcranial magnetic stimulation (TMS) of the left M1 preceded by right lateral cerebellum (CB) TMS at an interstimulus interval of 2 ms (CB→M1 PAS2 ms ) or 6 ms (CB→M1 PAS6 ms ) were applied. M1 excitability was assessed by motor-evoked potential (MEP) amplitude, short-interval intracortical inhibition (SICI), intracortical facilitation (ICF) and cerebellar inhibition (CBI) in the first dorsal interosseous muscle of the right hand before and after CB →M1 PAS. Results: In the healthy subjects, a significant MEP potentiation was found after the CB →M1 PAS2 ms protocol. In contrast, CB →M1 PAS6 ms resulted in suppression of the MEP amplitude. This phenomenon was not observed in the patients with SCA. SICI, ICF and CBI did not show any significant change in both groups. Conclusion: The current findings suggest that CB →M1 PAS-induced bidirectional STDP-like plasticity in M1 is significantly impaired in patients with SCA. The interpretation would be functional perturbation within the CDTC circuit in the patients with SCA.